What Is Communism? - Karen Latchana Kenney (Oxford, United Kingdom Capstone Global Library Ltd, 2018)
What is Communism and how does this political system work? This fascinating book looks at different aspects of Communism, explaining what they are, how they have come about and giving examples of such political systems in the world today.
Keywords: Non fiction